Paris : an electronic tour of the old city - Berger, Robert W. (Italica Press, Inc., 2006)
"A collection of written and visual descriptions of old Paris and its inhabitants, from Antiquity to the eighteenth century, arranged in chronological order; includes 46 color illustrations and over 30 texts, each with an introduction"--Provided by publisher